Coolie Types, Trinidad - (:unkn) unknown (Davidson and Todd., 2008)
Faded photograph of two East Indian men. Handwritten card.
Colour: Brown and White; Faded; Style: Portrait; Other: Divided
Keywords: Postcards; Trinidad and Tobago; Men--Trinidad and Tobago; East Indians--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago